Towards Development of a Dermal Pain Model: In Vitro Activation of Rat and Human Transient Receptor Potential Ankyrin Repeat 1 and Safe Dermal Injection of o‐Chlorobenzylidene Malononitrile to Rat. Issue 6 (7th July 2015) - Annas, Anita; Berg, Anna‐Lena; Nyman, Eva; Meijer, Thomas; Lundgren, Viveka; Franzén, Bo; Ståhle, Lars
Abstract: During clinical development of analgesics, it is important to have access to pharmacologically specific human pain models. o ‐Chlorobenzylidene malononitrile (CS) is a selective and potent agonist of the transient receptor potential ankyrin repeat 1 (TRPA1), which is a transducer molecule in nociceptors sensing reactive chemical species. While CS has been subject to extensive toxicological investigations in animals and human beings, its effects on intradermal or subcutaneous injection have not previously been reported. We have investigated the potential of CS to be used as an agonist on TRPA1 in human experimental pain studies. A calcium influx assay was used to confirm the capacity of CS to activate TRPA1 with >100, 000 times the selectivity over the transient receptor potential vanilloid receptor 1. CS dose‐dependently (EC50 0.9 μM) released calcitonin gene‐related peptide in rat dorsal root ganglion cultures, supporting involvement in pain signalling. In a local tolerance study, injection of a single intradermal dose of 20 mM CS to rats resulted in superficial, circular crusts at the injection sites after approximately 4 days. The histopathology evaluation revealed a mild, acute inflammatory reaction in the epidermis and dermis at the intradermal CS injection site 1 day after administration. After 14 days, the epidermal epithelium was fully restored. The symptoms were not considered to be adverse, and it is suggested that doses up to 20 μL of 20 mM CS can be safely administered to human beings. In conclusion, our data support development of a CS human dermal pain model.